Transformasi Lembaga Dakwah di Indonesia melalui Inovasi Kewirausahaan Sosial pada Pondok Pesantren Darunnajah - Muhammad Yudha Ardiansyah; Cecep Castrawijaya (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the transformation of Islamic da'wah institutions in Indonesia through social entrepreneurship innovation, focusing on the Darunnajah Islamic Boarding School in Jakarta. The aim is to understand how the Islamic boarding school adapts to socio-economic changes without abandoning its da'wah values. This study uses a library research methodology, referring to Kurt Lewin's (1947) theory of change, which consists of three stages: Unfreezing, Changing, and Refreezing. The findings indicate that during the Unfreezing phase, Darunnajah raises students' awareness of the need to develop traditional da'wah models. During the Changing phase, the Islamic boarding school implements social entrepreneurship innovations through various structures, such as cooperatives, Hajj travel agencies, and agribusiness. Finally, during the Refreezing phase, the values ​​of independence and professionalism are institutionalized within the boarding school's culture. Key factors contributing to its success are visionary leadership, a culture of student autonomy, and alumni support; obstacles encountered include internal resistance and a lack of resources. Overall, Darunnajah has succeeded in becoming an adaptive and productive model of modern da'wah that remains rooted in Islamic values.